Comparative oncology in action: vignettes on small molecule development. - LeBlanc, Amy.; Mazcko, Christina.; London, Cheryl.; Hergenrother, Paul J; Fan, Timothy M (Tufts University. Tisch Library., 2025)
Keywords: Comparative oncology, Drug development, Clinical trials, Small molecules.; Springer Open.